Identification of Tumor Microenvironment Genes in Triple Negative Breast Cancer - Mistry, Mittal; Vora, Hemangini (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: In triple negative breast cancer (TNBC) an aggressive molecular subtype of breast cancer, tumor microenvironment (TME) is a complex and dynamic ecosystem that plays a pivotal role in the tumor growth, disease metastasis, immune escape and therapeutic resistance. Understanding the TME holds significant potential for identification of biomarkers of TME and pathways associated as therapeutic targets for improving survival in patients with TNBC. Materials and Methods: The current study evaluated 682 TME related genes by Array Comparative Genomic Hybridization (aCGH) in 55 patients with TNBC. Results: Gain/amplification of 411 genes and loss/deletion of 196 genes of tumor microenvironment was observed in TNBC. Further PPI network analysis using Cytoscape plugin and degree ranking method identified GNAQ, MAPK1, AKT1, HRAS, and MAPK3 are five key up-regulated hub genes, and IL4, LCK, STAT6, MTOR, and NFKBIA are five key down-regulated hub genes. Conclusion: Gain/amplification of GNAQ and loss/deletion of LCK leads to activation of PI3K/AKT/mTOR and RAS/MEK pathways which can be targeted to improve survival of patients with TNBC. However, validation of these pathway genes by RT-PCR or protein expression by immunohistochemistry are further needed to establish these biomarkers as therapeutic targets for TNBC.